Educação Ambiental na Política de Assistência Social: a prática das ONGs no âmbito da proteção social básica em Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The environmental crisis shows several social and environmental consequences that are seen as demands of the socio-environmental issue, which are seen as expressions of the social question, since they result from the contradictions of the capitalist system and its mode of production and reproduction. Environmental Education is considered an important instrument in addressing socio-environmental issues and achieving sustainability. The object of this research is inserted in the discussion on Social Management in social network of the present time, which brings up a new format of relationship between State and civil society in the management of social policies. The policy focus of the study is the Social Assistance Policy (PNAS), in which it is verified that NGOs (as part of civil society) have access to the public fund to operationalize actions, services and / or projects in the scope of basic protection and special. In this sense, the research focused on the actions of Non-Governmental Organizations - NGOs of basic protection and practice of Environmental Education, aiming to analyze the practice of Environmental Education that is being developed by NGOs in the basic protection of Social Assistance in Manaus. Regarding methodological procedures, a documentary survey was carried out from the State Department of Social Assistance (SEAS) database, which showed that in 2014, a total of 26 NGOs accessed the public fund to develop Actions in Manaus, and through this information it was possible to identify eighteen NGOs that provided social assistance services in the scope of basic protection, and among these, three developed the practice of Environmental Education. In the second moment, field research was carried out in the three NGOs, where semi-structured interviews were conducted with the research subjects in the NGOs, which were the management agents (coordinators), technical agents (monitors) and users. Regarding the results of the research, it was evidenced that in the scope of basic social protection, the NGOs surveyed develop the practice of Environmental Education in a transversal way. In these circumstances, the insertion of Environmental Education in social-welfare services happens mainly through the approach of cross-cutting themes and is directly related to socio-educational activities. The theoretical / practical aspects that permeate the practice of Environmental Education were based on the conservative perspective. However, in this study it is understood that the practice of Environmental Education should be inserted in all activities developed by NGOs. It should be noted that the context of basic social protection constitutes a space conducive to the practice of Environmental Education, the Which must be developed in a critical, emancipatory and transformative perspective.
Keywords: Gestão Social; Assistência Social; Educação Ambiental; Crise Ambiental; CIÊNCIAS HUMANAS: SERVIÇO SOCIAL